Genome Editing for Plasmodesmal Biology - Iswanto, Arya Bagus Boedi; Shelake, Rahul Mahadev; Vu, Minh Huy; Kim, Jae-Yean; Kim, Sang Hee (Frontiers in Plant Science, 2021)
Plasmodesmata (PD) are cytoplasmic canals that facilitate intercellular communication and molecular exchange between adjacent plant cells. PD-associated proteins are considered as one of the foremost factors in regulating PD function that is critical for plant development and stress responses. Although its potential to be used for crop engineering is enormous, our understanding of PD biology was relatively limited to model plants, demanding further studies in crop systems. Recently developed genome editing techniques such as Clustered Regularly Interspaced Short Palindromic Repeats/CRISPR associate protein (CRISPR/Cas) might confer powerful approaches to dissect the molecular function of PD components and to engineer elite crops. Here, we assess several aspects of PD functioning to underline and highlight the potential applications of CRISPR/Cas that provide new insight into PD biology and crop improvement.